Reversals in the patterns of women's labor supply in the U.S., 1976 - 2009 - Diane J. Macunovich (Institute for the Study of Labor (IZA), 2009)
Despite strong increases in women's labor force participation - especially among married women with children - in the 1980s, and somewhat less strong increases in the 1990s, the first decade of the twenty-first century has seen declines across the board. These have been especially marked among single women, women with no children, and women with more than 16 years of education. Single women with no children have experienced declines of 7.2, 6.2 and 3.6 percentage points since the late 1980s, among women with less than 16, 16, and more than 16 years of education, respectively. Own-wage elasticities have increased since 2000, after decreasing in the previous 20 years, and the absolute value of cross-wage elasticities has also increased, after declining for at least 20 years. Despite this, the absolute value of elasticities with respect to the presence of children has for the most part continued to decline. Measured factors cannot explain the marked declines in hours worked that have been observed, suggesting that while the labor supply function was hypothesized to have shifted to the right in the 1980s and 1990s, it has shifted back to the left since the late 1990s. And the characteristics of single and childless women dropping out of the labor force after 1999 have changed: they on average had worked more hours, earned more per hour, enjoyed less other income, and had fewer children, than those who had dropped out prior to 1999.
urn:nbn:de:101:1-20091105835
Keywords: J21; 330; Women's labor force participation; women's labor supply; opt-out revolution; women's own-wage elasticities; effect of children on women's labor force participation; Frauenerwerbstätigkeit; Arbeitsangebot; Mütter; Lohn; Preiselastizität; USA